2022
DOI: 10.1177/0143831x221081167
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative job insecurity and extra-role behaviours: The moderating role of work motivation and perceived investment in employee development

Abstract: This article examines how qualitative job insecurity, work motivation and perceived investment in employee development (PIED) are associated with employees’ contextual performance in terms of extra-role behaviours (ERBs). The authors propose a three-way interaction model and suggest that the way qualitative job insecurity relates to employees’ ERBs is contingent upon their work motivation and PIED. Results showed that there was a significant three-way interaction between job insecurity, PIED and intrinsic moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…It is also well known that work motivation has a favorable function in mediating leadership style and organizational culture on doctors' performance. These findings are consistent with earlier studies from (Lee, 2019;Nikolova et al, 2022), which state that work motivation has a positive and significant effect on performance.…”
Section: Effect Of Work Motivation On Performancesupporting
confidence: 93%
See 2 more Smart Citations
“…It is also well known that work motivation has a favorable function in mediating leadership style and organizational culture on doctors' performance. These findings are consistent with earlier studies from (Lee, 2019;Nikolova et al, 2022), which state that work motivation has a positive and significant effect on performance.…”
Section: Effect Of Work Motivation On Performancesupporting
confidence: 93%
“…These results align with previous research from (Baig et al, 2019;Beauty & Aigbogun, 2022) that leadership style positively and significantly affects performance. Organizational culture can direct its members to achieve work performance (Nungchim & Leihaothabam, 2022;Tomic et al, 2017), and motivation become a source of energy for employees to providing their work performance (Lee, 2019;Nikolova et al, 2022).…”
Section: Effect Of Leadership Style Organizational Culture and Work M...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study relied on self-reported measures, which could lead to an overestimation of the results due to potential measurement errors [ 67 ]. Although common method bias has been addressed statistically, this limitation can be further examined by introducing a time delay in data collection [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Superiors and managers play an increasingly more critical role in employee motivation (Kaabomeir et al, 2022;Privara, 2022;Habes et al, 2021;Rowland et al, 2021). Theoretically and practically, it is vital to understand how leaders can enhance the pro-social motivation of pro-active employees and encourage them to support organisations by taking the lead (Xu et al, 2021;Galstyan et al, 2021;Nikolova et al, 2022). Employee relations arise from "working relationships" in the industrial environment.…”
mentioning
confidence: 99%